STRATEGI DINAS KOPERASI, USAHA KECIL DAN MENENGAH DALAM PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH DIKABUPATEN GIANYAR - Ariani, Ni Komang; Erviantono, Tedi; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2017)
Institutions that authorized in empowering micro small and medium enterprises are the cooperatives small and medium enterprises gianyar district. In an effort to empower micro small and medium enterprises there should be a proper strategy based on condition in the region. This study attempts to see how strategy implemented department of cooperatives medium gianyar cooperative district and he knows factors whatever support and impede in sector development micro small and medium enterprises. The methodology used the descriptive qualitative. From the analysis research, it is known that department of cooperatives medium cooperative district strategy gianyar have developed by the centralgoverment set forth in the stategic plan coperatives small and medium strategy bracing, strategy and development strategy protection. Keyword: empowerment, UMKM, Gianyar Regency